2003
DOI: 10.1111/j.1749-6632.2003.tb06048.x
|View full text |Cite
|
Sign up to set email alerts
|

Co‐Stimulatory Blockade in the Treatment of Murine Systemic Lupus Erythematosus (SLE)

Abstract: Although the life span of patients with systemic lupus erythematosus (SLE) has improved considerably over the last several decades, the toxicities of chronic immunosuppressive therapy are major causes of morbidity and mortality. Safer and more effective therapies for SLE are clearly needed. SLE is characterized by excessive activation of both B and T lymphocytes. Activation of these cells requires both antigen engagement and co-stimulatory signals from interacting lymphocytes (Carreno, B.M. M. Collins, 2002, A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 45 publications
0
25
0
Order By: Relevance
“…In preventive studies neither CTLA4-Ig, anti-CD40L, nor the combination of the two agents induced either a change in serum levels of Ig or a decrease in titers of IgM anti-DNA Abs, even in young mice (17,20,31). In contrast, these treatments inhibited class switching and somatic mutation and appeared to alter selection of autoreactive V region genes, consistent with their effect on delivery of T cell help to B cells (37). In remission induction studies, a 2-wk course of combination anti-CD40L and CTLA4-Ig did not induce remission in nephritic NZB/W F 1 mice (22).…”
Section: Discussionmentioning
confidence: 82%
“…In preventive studies neither CTLA4-Ig, anti-CD40L, nor the combination of the two agents induced either a change in serum levels of Ig or a decrease in titers of IgM anti-DNA Abs, even in young mice (17,20,31). In contrast, these treatments inhibited class switching and somatic mutation and appeared to alter selection of autoreactive V region genes, consistent with their effect on delivery of T cell help to B cells (37). In remission induction studies, a 2-wk course of combination anti-CD40L and CTLA4-Ig did not induce remission in nephritic NZB/W F 1 mice (22).…”
Section: Discussionmentioning
confidence: 82%
“…Steroids and immunosuppressants are currently used to treat many patients with SLE (20). The efficacy of these agents lies in their ability to suppress inflammation and to block or partially reduce abnormal T cell and B cell activation (21). Therefore, targeting both the B lymphocytes and the T lymphocytes as well as their interaction could represent an alternative approach to the currently available pharmacologic methods.…”
Section: Discussionmentioning
confidence: 99%
“…Long-term administration of CTLA4Ig as a fusion protein or expressed in adenovirus, to NZB/NZW F1 mice, prevented the onset of [9,10]. Gene therapy using this approach has also been shown to be beneficial in the MRL lpr/ lpr lupus mice [11]. Clinical studies with CTLA4Ig fusion protein showed improvement in rheumatoid arthritis activity when added to methotrexate therapy [12].…”
Section: Ctla4ig Fusion Proteinmentioning
confidence: 96%